EXPERIENCE OF THE CONTINUING PROFESSIONAL EDUCATION ACTIVITY MANAGEMENT AT THE INSTITUTE OF RADIATION HYGIENE - T. P. Simonova (Радиационная гигиена)
Results of the Institute of Radiation Hygiene educational activity during two and a half year since receiving a license are addressed in the article. Possibilities and approaches to the conduction of traditional and some unique training cycles are shown. Possible ways of educational activity enhancement are proposed.